Combating Nutrient Deficiency in Pakistan (The Pakistan Development Review, 2016)
To quantify the micronutrient deficiencies and their overtime trends, food quantities reported to be consumed in HIES surveys data during 1991-92 and 2011-12 are converted into major and micronutrients using the FAO Food Composition Table for Pakistan. To see the impact of different price and income support policies on micronutrient consumption, nutrient demand elasticities are estimated for 2011-12 for carbohydrates (energy), protein, calcium, vitamin A, vitamin C, vitamin B1, vitamin B2, and Niacin. The Almost Ideal Demand System (AIDS) is applied to estimate the demand elasticities of the eight food groups which are then converted into nutrient demand elasticities using the transformation of Hunag (1996). On average, per capita consumptions of almost all micronutrients are deficient compared to their respective recommended levels. Our analysis suggest that income support to the poor in Pakistan through programmes like BISP would have been much more effective to eradicate nutrient deficiency, if deficient nutrient(s) are targeted and support is provided to those foods having highest demand elasticity for that nutrient. For example, the promotion of wheat and other cereals are important to eradicate energy deficiency, and promotion of vegetables, fruits, and milk are particularly important in eradicating vitamin A, C and iron deficiencies. These commodities are also high value crops for farmers, thus the price support in these crops will also impact micronutrient consumption through income effect.